A simulation-based methodology for the analysis of the effect of lean tools on energy efficiency: An application in power distribution industry. (20th February 2019) - Baysan, Serdar; Kabadurmus, Ozgur; Cevikcan, Emre; Satoglu, Sule Itir; Durmusoglu, Mehmet Bulent
Abstract: In recent years, there has been an increasing interest in energy consumption in manufacturing systems due to the rising environmental awareness in society as well as the necessity of being cost-effective in the global competitive environment. Companies have to take measures to decrease their unnecessary energy consumption while maintaining their throughput. In this context, lean manufacturing is regarded as one of the most significant management initiatives for energy management, since it intensifies the effective utilization of resources via the identification and elimination of wastes. In this paper, a holistic methodology, which integrates Energy Value Stream Mapping, experimental design and simulation, is developed with the aim of analyzing and reducing the energy consumption within Lean Transformation. Moreover, the effects of unevenness (mura) and overburden (muri), as root causes of waste (muda), on energy consumption has been addressed for the first time. The proposed methodology is applied to a real-life cable ladder manufacturing system and its feasibility is demonstrated. The results of the application showed that the adaptation of cellular manufacturing, pull system and mistake-proofing yielded approximately 72.37% reduction in energy consumption. Highlights: A holistic method to analyze the energy consumption during the Lean Transformation. The method integrates Energy Value Stream Map, experimental design and simulation. The effects of lean tools on energy are analyzed by simulation for the first time. The study has a real industrial application for an electrical products manufacturer. The real-life application revealed that lean tools reduce the energy consumption.